Size-Fractionated Contribution of Microbial Biomass to Suspended Organic Matter in the Eastern Tropical South Pacific Oxygen Minimum Zone - Cantarero, Sebastian I.; Henríquez-Castillo, Carlos; Dildar, Nadia; Vargas, Cristian A.; von Dassow, Peter; Cornejo-D’Ottone, Marcela; Sepúlveda, Julio (Frontiers in Marine Science, 2020)
Cell membrane intact polar lipids (IPLs) are chemotaxonomic biomarkers whose abundances and distributions in water column environments reflect the living biomass of in situ microbial communities, and can be used to determine the relative contribution of distinct functional and phylogenetic groups to water column carbon stocks. The diversity of IPLs in marine environments is however vast, while our knowledge of their biological origins remains limited. Here, we study the distribution of IPLs in size-fractionated suspended organic matter from the oxygen minimum zone (OMZ) of the eastern tropical South Pacific (ETSP) off northern Chile. Canonical correspondence analyses of total IPL abundances and water column physiochemistry demonstrate distinct distributions of microbial sources associated with different geochemical regions in the water column (chlorophyll maximum, upper chemocline, lower chemocline, upper OMZ, core OMZ, and mesopelagic region). Furthermore, the distribution of IPLs in free-living (0.3–2.7 µm) and particle-attached (2.7–53 µm) suspended organic matter differs, suggesting distinct biological sources in each size fraction. While some parallels exist, the diversity and distribution of IPLs in the OMZ system of the ETSP off northern Chile exhibited some unique features compared to other OMZ systems; for instance, we observed a significantly lower contribution of betaine lipids from phytoplanktonic sources, possibly reflecting a physiological response to severe N-limitation in this area. The overall IPL abundance in the two size fractions also indicates a dominance of free-living biomass in the OMZ and mesopelagic regions, suggesting that these areas of the water column could provide additional sources of submicron organic carbon to deeper waters. This study improves the utility of IPLs as chemotaxonomic biomarkers by providing insight into the contrasting distributions of microbial biomass from different life modes (free-living and particle-attached). Our results suggest that microbial production in low oxygen environments may be more important to total water column carbon stocks than previously thought.